Impact and Liberty Rates and Mixtures for Efficacy in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of the study was to compare Impact (topramezone), Liberty (glufosinate) and a premixture of the two herbicides (Sinate) for efficacy in corn. Rates for each herbicide were 0.75 and 1.0 oz/a for Impact, 22 and 30 oz/a for Liberty, and 21 and 28 oz/a for Sinate. Impact and Sinate, each at the high rates, and Status plus glyphosate provided the best kochia control for corn late in the season. These treatments, along with the low rate of Impact controlled crabgrass the best. Status was also the best treatment for Russian thistle, Palmer amaranth, and green foxtail control. The high rate of Impact also controlled Russian thistle well, whereas the high rate of Sinate provided good foxtail control. Most herbicide treatments increased grain yields relative to the untreated control, but yields were decidedly greater with Status plus glyphosate.
Keywords: herbicide resistance; corn